La fabrique du patrimoine gastronomique dans les musées départementaux de l’Ain : une aventure croisée entre botanique, histoire, ethnologie et arts - Delphine Cano (In Situ, 2019)
The Ain department is well known as a land of gastronomy. The celebrated French author and gastronome Jean-Anthelme Brillat-Savarin was born there and gourmets call two of its regions, Bresse and Bugey, lands of culinary ‘perfection’. The department is a place of exchanges and circulation between the Rhône Valley, Switzerland and Burgundy, largely dedicated to supplying food to neighbouring cities. The Bresse region, in particular, has a local identity built on the fame of its products, including its well-known Bresse poultry with its AOP label (protected designation of origin). Today, the Bresse Museum at Saint-Cyr-sur-Menthon is particularly keen to promote the gastronomic heritage as part of a general policy of encouraging tourism in the department. This is also a continuation of a policy of collecting, preserving and promoting the local and national gastronomic heritage initiated by the Ain museums service some 35 years ago. A retrospective analysis of these initiatives paints a rich picture of exchanges between different approaches and disciplines and underlining the specific history of the department’s museums: collections of local and rare plant varieties in the garden of the Revermont Museum; agriculture, menus and figures of famous chefs at the Bresse Museum; food gathering and cooking in the spirit of Brillat-Savarin and the American author Gertrude Stein in Bugey; fishing and hunting in the Dombes; smuggling in Gex; wartime food practices at the Nantua Museum of Resistance and Deportation; the food of ordinary working men and women at the Bonnet silk factory in Jujurieux. The intersection of all these actions makes it possible to approach the notion of gastronomic heritage in all its aspects and all its complexity. We can follow its evolution through a period in which the whole field of heritage has seen considerable diversification and during which museums of society have also evolved. Today, the gastronomic heritage has become a shared heritage at the heart of various societal issues, including climate change and democracy.